2013
DOI: 10.1039/c3sc51253c
|View full text |Cite
|
Sign up to set email alerts
|

Combining 3D printing and liquid handling to produce user-friendly reactionware for chemical synthesis and purification

Abstract: We use two 3D-printing platforms as solid-and liquid-handling fabricators, producing sealed reactionware for chemical synthesis with the reagents, catalysts and purification apparatus integrated into monolithic devices. Using this reactionware, a multi-step reaction sequence was performed by simply rotating the device so that the reaction mixture flowed through successive environments under gravity, without the need for any pumps or liquid-handling prior to product retrieval from the reactionware in a pure for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 33 publications
(32 reference statements)
0
110
0
2
Order By: Relevance
“…24 For example, Kitson et al [25][26][27] demonstrated fluidic devices 3D printed by extruding plastic through a heated nozzle. However, this fabrication method is inherently unable to produce feature sizes and flow channel dimensions needed for microfluidic (as opposed to macrofluidic or millifluidic) device fabrication.…”
Section: Microfluidicsmentioning
confidence: 99%
“…24 For example, Kitson et al [25][26][27] demonstrated fluidic devices 3D printed by extruding plastic through a heated nozzle. However, this fabrication method is inherently unable to produce feature sizes and flow channel dimensions needed for microfluidic (as opposed to macrofluidic or millifluidic) device fabrication.…”
Section: Microfluidicsmentioning
confidence: 99%
“…[17][18][19] Considerable progress has been made in demonstrating the utility of 3D printing in the chemical sciences in the "reactionware" series of publications. [20][21][22] Herein we explore the revolutionary device fabrication potential of 3D printing applied to the aforementioned challenges of the design and manufacture of electrolyser components, resulting in a new manufacturing paradigm wherein 3D printed components are, for the rst time, incorporated into an electrolyser.…”
mentioning
confidence: 99%
“…A month later (Jun 2013) the group attempted to make liquid and solid handling devices, using PP and the Bits from Bytes 3DTouch™ 3D printer to produce a serious of interconnecting reaction chambers. 123 The reaction reagents, catalysts, and purification apparatus were integrated into a single monolithic device. This allowed a multi-step reaction sequence to be performed by simply rotating the device so that the reaction mixture could flow through successive environments under gravity.…”
Section: Additive Manufacture Of Fluidic Devicesmentioning
confidence: 99%
“…This process can be used with a range of commercially available thermoplastic polymers, and has been utilised to produce a number of fluidic reaction devices. 123 Resistive heaters within the nozzle maintain the temperature of the polymer at a temperature just above its melting point, as the filament is fed through the nozzle by a motorised wheel. The material is usually supplied in the form of a long filament, but some machines utilise plastic pellets dispensed through a hopper.…”
Section: Introductionmentioning
confidence: 99%